The medical simulation markup language: simplifying the biomechanical modeling workflow - Suwelack, Stefan; Stoll, Markus; Schalck, Sebastian; Schoch, Nicolai; Dillmann, Rüdiger; Bendl, Rolf; Heuveline, Vincent; Speidel, Stefanie (Medicine meets virtual reality 21, 2014)
Modeling and simulation of the human body by means of continuum mechanics has become an important tool in diagnostics, computer-assisted interventions and training. This modeling approach seeks to construct patient-specific biomechanical models from tomographic data. Usually many different tools such as segmentation and meshing algorithms are involved in this workflow. In this paper we present a generalized and flexible description for biomechanical models. The unique feature of the new modeling language is that it not only describes the final biomechanical simulation, but also the workflow how the biomechanical model is constructed from tomographic data. In this way, the MSML can act as a middleware between all tools used in the modeling pipeline. The MSML thus greatly facilitates the prototyping of medical simulation workflows for clinical and research purposes. In this paper, we not only detail the XML-based modeling scheme, but also present a concrete implementation. Different examples highlight the flexibility, robustness and ease-of-use of the approach.
Gesehen am 26.01.2021